Analysis of Organizational Behavior on Marketing Strategy in Facing Business Competition in the Digital Era among MSMEs in Soppeng Regency - Ibrahim Ibrahim; Amrial Amrial; Rismayuliana Rismayuliana; Rahmatan Rahmatan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
This research aims to analyze in depth the influence of organizational behavior on digital marketing strategies among Micro, Small, and Medium Enterprises (MSMEs) in the Soppeng Regency area in facing the dynamics of business competition in a massive technological transformation era The research approach used is qualitative descriptive with data collection techniques through participatory digital observation and documentation studies of the cyber business activities of local entrepreneurs in Soppeng. The focus of the observation is directed at the dimensions of work discipline, digital literacy, and adaptive behavior of individuals within the organization as the main driving variables for the effectiveness of local product promotion. The results show that professional and disciplined organizational behavior in managing digital content in the Soppeng Regency area contributes significantly to increasing brand awareness and customer engagement across various social media platforms. The digital literacy of business actors in Soppeng is proven to be an innovation engine that allows market reach to expand beyond conventional geographical boundaries, thereby strengthening the bargaining position of local products on the national stage. The synergy between planned real actions and intelligent utilization of cyber technology is the main key to the economic sustainability of MSMEs in Soppeng Regency to achieve robust competitive advantage amidst the continuous flow of digitalization This research provides strategic implications regarding the importance of strengthening human resource capacity based on adaptive-digital organizational behavior as a foundation for community economic growth in the region.